Policing, Practical Knowledge and Urban Management: Public Lighting in Mexico City (late 18th - early 19th century) - Arnaud Exbalin (Nuevo mundo - Mundos Nuevos, 2019)
In order to study and reconsider the shift of the science, knowledge and technics between the colonial empire and the European nations, we focused on the administrative sciences at the turn of the 18th-19th century, the precise time where they modernized more precisely in the town of Mexico. For the colonial administration, the term “police” means policing, that is to say, the good and fair governance of towns. That polysemic concept being new, is considered on two aspects: its practices, work of maintenance and good functioning by a new figure, the sereno also named guardafarol, which explains his job and the urban furniture they use, in that case lanterns. From 1790 more than 1000 lanterns were installed in Mexico City. First this article is about the circulation of scientific and technical knowledge about the street light device, because this knowledge developed very rapidly with a surprising synchrony all through the European capitals but also in the Spanish colonies. The second aspect of the article is about the positive consequences on the urban management or policing because permanent street lighting at night creates a feeling of security for the people and it makes the town secured.